2022
DOI: 10.3390/ijerph192013358
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Cytisine in Combination with a Community Pharmacists’ Counselling for Smoking Cessation in Thailand: A Randomized Double-Blinded Placebo-Controlled Trial

Abstract: Background: Cytisine is a prospective pharmacological alternative for community pharmacy smoking cessation services. However, it has not yet been licensed because of a lack of efficacy and safety information in Thailand. Objective: The aim of this study was to evaluate the efficacy of cytisine in combination with community pharmacists’ counselling on smoking cessation in a community pharmacy in ThailandDesign. Setting, participants, and interventions: A double-blinded randomized placebo-controlled trials was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 14 publications
(20 reference statements)
0
18
0
Order By: Relevance
“…Eight RCTs [10–13, 15, 17, 19, 20] compared cytisine to placebo at the standard dose covering 5922 patients, 2996 of whom took cytisine, delivering a RR of 2.25, 95% CI = 1.42–3.56 (Figure 4: Forest plot of comparison: 1, cytisine versus placebo; outcome, 1.1 smoking cessation rate at longest follow‐up, with a high level of heterogeneity ( I 2 = 88%). Following sensitivity analysis, we pooled the findings of only five RCTs [11–13, 19, 20] covering 2134 patients, 1099 of whom took cytisine, delivering an RR of 3.46, 95% CI = 2.45–4.89 (Figure 5: Forest plot of comparison: 1, cytisine versus placebo, sensitivity analysis of outcome, 1.1) with a level of heterogeneity not relevant ( I 2 = 18%). Also following the sensitivity analysis, by removing from the analysis the trials classified as having a high risk of bias [14, 15], the effect estimates were unchanged (RR = 2.86; 95% CI = 1.73–4.73) and decreased the I 2 value to 9%.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Eight RCTs [10–13, 15, 17, 19, 20] compared cytisine to placebo at the standard dose covering 5922 patients, 2996 of whom took cytisine, delivering a RR of 2.25, 95% CI = 1.42–3.56 (Figure 4: Forest plot of comparison: 1, cytisine versus placebo; outcome, 1.1 smoking cessation rate at longest follow‐up, with a high level of heterogeneity ( I 2 = 88%). Following sensitivity analysis, we pooled the findings of only five RCTs [11–13, 19, 20] covering 2134 patients, 1099 of whom took cytisine, delivering an RR of 3.46, 95% CI = 2.45–4.89 (Figure 5: Forest plot of comparison: 1, cytisine versus placebo, sensitivity analysis of outcome, 1.1) with a level of heterogeneity not relevant ( I 2 = 18%). Also following the sensitivity analysis, by removing from the analysis the trials classified as having a high risk of bias [14, 15], the effect estimates were unchanged (RR = 2.86; 95% CI = 1.73–4.73) and decreased the I 2 value to 9%.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the analysis remained robust in other summary statistics, delivering an OR of 2.62 (95% CI = 1.52-4.49; I 2 = 27%). These trials reported smoking cessation at the longest follow-up: at 24 weeks [11], 48 weeks [20],…”
Section: Smoking Cessation Rate At Longest Follow-upmentioning
confidence: 99%
See 3 more Smart Citations